Post-mortem Computed Tomographic Angiography in Equine Distal Forelimbs: A Feasibility Study - Blaettler, Chantal; Kaessmeyer, Sabine; Grabherr, Silke; Koch, Christoph; Schweizer, Daniela; Van der Vekens, Elke (Frontiers in Veterinary Science, 2022)
In-depth understanding of pathophysiological processes occurring in the vasculature of the equine distal limb is of great importance to improve both diagnostic and therapeutic approaches to diseases. To gain further insights, a model allowing high-resolution 3D-visualization of the vasculature is necessary. This pilot study evaluated the feasibility of restoring vascular perfusion in frozen-thawed distal equine cadaver limbs without prior preparation using computer tomographic imaging (CT). Five frozen-thawed, radiographically normal forelimbs were perfused with a lipophilic contrast agent through the median artery and radial vein in three phases (arterial, venous, and arterial-venous combined (AVC) dynamic). For comparison, one additional limb was perfused with a hydrosoluble contrast agent. The CT-studies (16-slice MDCT, 140 kV, 200 mA, 2 mm slice thickness, 1 mm increment, pitch 0.688) were evaluated at 11 specified regions for visualization of the vasculature and presence of artifacts or anatomic variations. The protocol used in this study proved to be feasible and provided good visualization (93.1%) of vasculature with low rates of artifacts. During the different phases, vascular visualization was similar, but while filling defects decreased in the later phases, extravasation worsened in the 2 limbs where it was observed. Subjectively, the best quality of angiographic images was achieved during the AVC dynamic phase. Perfusion with hydrosoluble contrast resulted in significantly lower vascular visualization (74.0%) and higher artifact rates. This study shows that reperfusion of frozen-thawed equine distal limbs with a lipophilic contrast agent allows for high-quality 3D-visualization of the vasculature and may serve as a model for in situ vascular evaluation in the future.